2009
DOI: 10.14430/arctic341
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical Evidence for the Grass (Poaceae) Species of Pleistocene Beringian Lowlands

Abstract: ABSTRACT. Late Pleistocene Beringia had herb-dominated vegetation with abundant grasses (Poaceae), and it was inhabited by an impressive assemblage of large grazing mammals. This paper reconstructs the list of most probable late Pleistocene Beringian lowland grass species from biogeographical evidence. Late Pleistocene eolian sediments and buried soils indicate that large areas of the Beringian lowlands had nutrient-rich, silty soils that occurred over ice-rich permafrost but were generally not waterlogged. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Widespread well-drained soil conditions (Guthrie, 2001;Swanson, 2006;Viau et al, 2008). Widespread well-drained soil conditions (Guthrie, 2001;Swanson, 2006;Viau et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Widespread well-drained soil conditions (Guthrie, 2001;Swanson, 2006;Viau et al, 2008). Widespread well-drained soil conditions (Guthrie, 2001;Swanson, 2006;Viau et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Much Arctic research is conducted in locations that are physically distant from communities and places that community members frequently visit (e.g., Abnizova and Young 2010), involves geological time periods that are temporally distant from the experience and oral histories of contemporary people (e.g., Swanson 2006), involves physical and biological phenomena that are distant from the primary interests and knowledge of local people (e.g., Gradinger and Bluhm 2010), and involves methodologies that are distant from the expertise and interests of nonscientists (e.g., Laidler et al 2008).…”
Section: Prevalence Of Mode 1 and Mode 2 Research In Arctic Sciencementioning
confidence: 99%
“…Anderson, 1985Anderson, , 1988Anderson et al, 1988;Anderson and Brubaker, 1994). Overall, the pollen assemblages corresponding to the cold and dry late Pleistocene conditions in the lowlands of Beringia are dominated by Poaceae (Swanson, 2006). Recent macrofossil and DNA analyses have indicated that there might have been a higher proportion of forbs than was previously thought based on pollen analysis, which tends to underestimate actual vegetation diversity by over-representing high pollen-producers such as the herbs from the Poaceae, Cyperaceae and Artemisia genera (Willerslev et al, 2014).…”
Section: Introductionmentioning
confidence: 99%